2,2′-Bi[6,6′-dimethyldibenzo[d,f][1,3]dioxepine] - Zhang, Hai-Quan (International Union of Crystallography, 2008)
The title compound, C(30)H(26)O(4), is a dimer of 6,6′-dimethyldibenzo[d,f][1,3]dioxepine linked by formation of a C—C bond in the para position with respect to one O atom. The dimer is arranged around an inversion centre. As is usually observed in related compounds, the dibenzo group is twisted, the two benzene rings making a dihedral angle of 41.56 (9)°. The seven-membered ring exhibits a twisted conformation.